Whole genome sequence analyses of Indonesian isolates SARS‐CoV‐2 variants and their clinical manifestations - Elnora Listianto Lie; Tedi Dwi Fauzi Hermawan; Kholis Abdurachim Audah (Indonesian Journal of Biotechnology, 2023)
The SARS‐CoV‐2 virus has been the cause of the global pandemic since the end of 2019. Since then, the virus has mutated to create different types of variants with numerous effects on those infected. This has complicated human intervention for prevention. Indonesia was heavily affected by the pandemic, specifically from May to August 2021, and as a country has recorded many distinct isolates. Thus, characterization of the virus strains from Indonesia is important. GISAID, NCBI BLAST, and MAFFT version 7 were used. There were 9,488 isolates in Indonesia as of November 2021, with the majority including the Delta variant. While most of the isolates have mutations common to those from other countries, there are some atypical ones, such as mutation V1264L in the Delta variant that was suspected to play a role in worsening the pandemic. The Delta variant had the most mutations in the spike protein when compared to the Alpha and Beta variants, giving it important roles in infectivity and vigorous entry into cells, with some general clinical manifestations like fever and sore throat; however, the severity of the Delta variant is attributable to its rapid growth. This is why, from May to November 2021 in Indonesia, cases of the Delta variant rocketed, unlike the other variants.